Knowledge of Dementia: Do family members understand dementia as a terminal condition? - Andrews, S.; McInerney, F.; Toye, Christine; Parkinson, C.; Robinson, A. (2015)
Current research identifies advanced dementia to be the terminal phase of this progressive and incurable condition. However, there has been relatively little investigation into how family members of people with advanced dementia understand their relative's condition. In this article, we report on semi-structured interviews with 10 family members of people with advanced dementia, in a residential aged care facility. Using a qualitative, descriptive design, we explored family members' understandings of dementia, whether they were aware that it was a terminal condition, and the ways they developed their understandings. Findings revealed that the majority of family members could not recognize the terminal nature of dementia. Relying on predominantly lay understandings, they had little access to formal information and most failed to conceptualize a connection between dementia and death. Moreover, family members engaged in limited dialogue with aged care staff about such issues, despite their relatives being in an advanced stage of the disease. Findings from our study suggest that how family members understand their relative's condition requires greater attention. The development of staff/family partnerships that promote shared communication about dementia and dying may enhance family members' understandings of the dementia trajectory and the types of decisions they may be faced with during the more advanced stages of the disease.